Cfd Analysis of 58 Adit Main Fans Parallel Installation for the 2015–2019 Underground Developments of the New Level Mine Project - Hurtado-Cruz, J (Elsevier Ltd, 2015)
The New Level Mine project (NLMP), the planned underground expansion of the El Teniente mine in Rancagua, Chile, is expected to reach a daily extraction rate between 137 and 180 ktpd upon achieving full capacity. Production is planned to start in the year 2019. To achieve the 2015 to 2019 underground development schedule, the ventilation requirements were estimated to be in the range of 944 m3/s (2000 kcfm). To provide the airflow volume required, 189 m3/s (400 kcfm) has to be provided by the El Teniente mine, and the remaining by the main 74 and 75 Adits, currently in the final stage of their construction phase. However, providing the 189 m3/s (400 kcfm) will require significant modifications to the current system of El Teniente. As a result, a number of alternatives were explored, including adding raises to generate parallel airways and installing fans to reinforce the current ventilation system. From the alternatives studied, the installation of a second main fan (system) in parallel to an existing one was identified as the best operational solution and selected for implementation. However, the location and expected geometry of the ventilation circuit was not ideal and there were concerns as to the operation of both fans once the second fan was installed and commissioned. This paper presents the study used to estimate the operating points of both the current and the new fan, and to justify the parallel installation of the additional main fan. An additional computational fluid dynamics study was undertaken to validate the operating point, given the particular geometry of the fan s location and placement, to guarantee a stable operation of the fans. © 2015 Elsevier Ltd